The German anti-Keynes? On Walter Eucken's macroeconomics - Lars P. Feld; Ekkehard A. Köhler; Daniel Nientiedt (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2018)
Germany's approach to solving the Eurozone crisis is supposedly based on the ideas of Walter Eucken (1891-1950), the founder of ordoliberalism. In this and other contexts, Eucken's work has been described as being in direct opposition to that of John Maynard Keynes. Our paper aims to clarify and differentiate the relationship between the two scholars by making two main points. First, we show that Eucken supported a proto-Keynesian stimulus programme at the height of the Great Depression, the so-called Lautenbach plan of 1931. Second, we critically examine Eucken's description of 'full employment policy', a strategy with obvious parallels to Keynesian economic policy. Additionally, the paper maintains that when comparing Eucken and Keynes, more emphasis should be given to the fact that the former favours a rule-based rather than discretionary approach to policy-making.
Keywords: B31; D78; E63; 330; Ordoliberalism; Eurozone Crisis; Monetary Policy; Fiscal Policy; History of Economic Thought